Wealth Preference and Rational Bubbles - Jean-Baptiste Michau; Yoshiyasu Ono; Matthias Schlegl (Center for Economic Studies and ifo Institute (CESifo), 2018)
We consider a neoclassical economy where households derive utility from holding wealth. We show that, under some conditions, there can be rational bubbles. Hence, we provide a microfoundation for bubbles that relies on a frictionless infinite-horizon economy without any heterogeneity across households. While our bubbly equilibria are very similar to those obtained by Tirole (1985) in an overlapping generation economy, the underlying economics is different. Turning to public debt, we show that Ponzi schemes can be sustainable. Hence, in general, the limit on the accumulation of public debt by the government is not given by its no-Ponzi condi-tion but, instead, by the representative household's transversality condition. The Ricardian equivalence must hold in any of our equilibria. Finally, in the presence of money, the real equilibrium structure of the economy remains unchanged. We carefully investigate the effects of helicopter drops of money on the possibility of Ponzi schemes and of speculative hyperinflation or deflation.
Keywords: E13; E44; G12; 330; Ponzi scheme; rational bubble; wealth preference